Functional Outcome of Open Surgical Release Versus Percutaneous Release of Tennis Elbow. - Gyawali, Bidur; Bhatta, Toya Raj; Dawadi, Tej Prakash; Shrestha, Suman Kumar; RC, Dhirga Raj; Pradhan, Nabees Man Singh (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: Tennis Elbow is a familiar term used to describe myriad of symptoms around the lateral aspect of the elbow. It occurs more frequently in non-athletes than athletes. Tennis elbow has a reported prevalence of 2% in the general population. It is most commonly seen in patients between the ages of 30 and 50 years. Tennis Elbow is considered resistant if it fails to respond to conservative means of treatment for at least six months. Methods: Patients meeting the criteria were divided randomly into two groups of open surgical release and percutaneous release using random number generator software and respective surgery was done. Functional score, time to return to pre-injury status and patient satisfaction were noted at two months and six months follow up. Results: Among 62 patients (34 female, 28 male) enrolled, 32 patients (mean age 42.5 years) were allocated to open group and 30 patients (mean age 44.2 years) were allocated to percutaneous group. At two months follow up, 81% of open group had excellent to good score and 19% of cases had fair score as compared to 90% cases of percutaneous group with excellent to good score and 10%with fair score (p = 0.376). At six months follow up, both open and percutaneous group had 90% excellent to good results and 10% fair results (p = 0.596). The mean time to return to work of open release was 6.03 weeks and percutaneous release was 2.3 weeks (p = 0.0001). Conclusions: Percutaneous release and open surgical release in surgical management of resistant tennis elbow have statistically similar functional outcome. The time to return to work after percutaneous release is significantly earlier.